2018
DOI: 10.22270/jddt.v8i4.1752
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of Controlled Porosity Osmotic Tablets of Garcinia Indica Extract

Abstract: The present study deals with the development and evaluation of controlled porosity osmotic pump (CPOP) tablets containing inclusion complexes of methanolic extract of Garcinia indica fruit rind. Wet granulation method was used for the development of core tablets. Core tablets were incorporated with different concentrations of sodium chloride as osmogen and additives. The CPOP tablets were coated with cellulose acetate as a wall forming material and HPMC acts as pore forming material in SPM. The formulated tabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…P-values for the response were found to be less than 0.0500 indicate model terms are signi cant whereas values greater than 0.1000 indicate the model terms are not signi cant the results recorded showed VGH 12 was the optimized formulation (Jagtap et al, 2018).…”
Section: Optimization Of Formulationmentioning
confidence: 88%
“…P-values for the response were found to be less than 0.0500 indicate model terms are signi cant whereas values greater than 0.1000 indicate the model terms are not signi cant the results recorded showed VGH 12 was the optimized formulation (Jagtap et al, 2018).…”
Section: Optimization Of Formulationmentioning
confidence: 88%
“…In a recent study by Arefhosseini et al (2022), it was demonstrated that the consumption of GC for 8 weeks led to a significant reduction in TG, the TG/HDL‐C ratio, and LDL‐C among overweight and obese females with NAFLD in the GC group when compared to the control group. In a separate RCT, the consumption of GC for a duration of 3 months resulted in improved lipid profiles, which included reductions in TC, TG, and VLDL levels among obese individuals with a BMI of 30 or higher (Jagtap et al, 2015). Preuss et al also reported significant reductions in serum TC and TG levels and increases in HDL in moderately obese individuals following 4667 mg HCA for 8 weeks (Preuss, Bagchi, Bagchi, Rao, Dey, et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the literature research, various pharmacological activities of G. indica were reported and reviewed [33][34][35], and a total of 7 papers were additionally reported recently. We comprehensively reviewed and updated the study design, results, and interpretation of each paper.…”
Section: Methodsmentioning
confidence: 99%
“…G. indica contains a major active compound called garcinol. This component is a yellow-colored, fat soluble pigment found in the rinds of G. indica at a level of 2-3%, which can be separated from the fruit rinds by EtOH and hexane extraction [35]. Garcinol shows powerful antioxidant activity, since it contains both phenolic hydroxyl groups and a β-diketone moiety, and in this respect, it resembles the structure of curcumin [48].…”
Section: Pharmacological Effects Of Garcinol a Major Active Constituent From G Indicamentioning
confidence: 99%